2022
DOI: 10.1039/d2cc01382g
|View full text |Cite|
|
Sign up to set email alerts
|

CoH-catalyzed radical hydroalkylation of alkenes with 1,3-dicarbonyls

Abstract: Metal-hydride hydrogen atom transfer (MHAT) catalysis has emerged as a useful reaction platform for alkene hydrofunctionalization with high chemoselectivity and predictable branched selectivity. However, MHAT-mediated hydrofunctionalization involves carbon−carbon bond formation...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 49 publications
0
4
0
Order By: Relevance
“…Very recently, the Zhang research group reported the intermolecular hydroalkylation of different alkenes 174b with various 1,3-dicarbonyls 174a to construct C(sp 3 )–C(sp 2 ) under Co-catalysis (Scheme 174). 273 Depending on the substrate, cobalt-complexes 174d or 174e were used in the presence of TMFP-BF 4 , TMDSO in toluene or THF solvent. The protocol showed wide functional group tolerance and could be operated under mild reaction conditions.…”
Section: Alkylation Via C–h Bond Activationmentioning
confidence: 99%
“…Very recently, the Zhang research group reported the intermolecular hydroalkylation of different alkenes 174b with various 1,3-dicarbonyls 174a to construct C(sp 3 )–C(sp 2 ) under Co-catalysis (Scheme 174). 273 Depending on the substrate, cobalt-complexes 174d or 174e were used in the presence of TMFP-BF 4 , TMDSO in toluene or THF solvent. The protocol showed wide functional group tolerance and could be operated under mild reaction conditions.…”
Section: Alkylation Via C–h Bond Activationmentioning
confidence: 99%
“…In aliphatic systems, the use of metal-catalyzed hydrogen atom transfer (MHAT, Scheme B) has enabled the hydrofunctionalization of alkenes with high regioselectivity . Further, use of cobalt-salen catalysts in the presence of an oxidant generates cation-like reactivity from the radical through radical-polar crossover (Scheme B). This suggests that a cobalt-salen system for MHAT to 2-azadienes would be a feasible and novel route to 2-azaallyl cation equivalents. Here, we show that oxidative MHAT can be used to form hemiaminal ethers and esters via intermolecular hydroalkoxylation and hydrocarboxylation (Scheme ).…”
mentioning
confidence: 99%
“…Oxidative MHAT hydrofunctionalizations have been demonstrated with a number of alkenes in a series of impactful papers. Interestingly, these almost always use an excess of the nucleophilic trap. With the 2-azadiene reactions described here, on the other hand, it was possible to accomplish the coupling reaction using only 1.2 equiv of nucleophile.…”
mentioning
confidence: 99%
“…Herein, we report a mechanistically distinct, radical–polar crossover strategy , for the generation of indeno­[1,2- c ]­furans (Scheme C). This protocol features a catalytic system of a Co­(salen) complex and N -fluorobenzenesulfonimide (NFSI), which readily undergoes single-electron transfer to generate an amidyl radical as the competent hydrogen-atom transfer agent to react with β-dicarbonyl to afford the corresponding vinyl radical and ultimately the anticipated polycyclic indeno­[1,2- c ]­furans via sequential intramolecular radical and polar cyclizations (see the related mechanistic experiments in Scheme S1). …”
mentioning
confidence: 99%